2018
DOI: 10.1155/2018/1672621
|View full text |Cite
|
Sign up to set email alerts
|

Low Total Dose of Anti-Human T-Lymphocyte Globulin (ATG) Guarantees a Good Glomerular Filtration Rate after Liver Transplant in Recipients with Pretransplant Renal Dysfunction

Abstract: We aimed to evaluate the safety and efficacy of low doses of anti-T-lymphocyte globulin (ATG)-based immunosuppression in preserving renal function and preventing liver rejection in liver transplant (LT) recipients with pretransplant renal dysfunction. We designed a prospective single-center cohort study analyzing patients with pre-LT renal dysfunction defined as eGFR<60 mL/min/1.73m2, who underwent induction therapy with ATG (ATG group, n=20). This group was compared with a similar retrospective cohort treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…In KT recipients, recently published economic evaluations of NDI and DI have been favorable, with ATG often being preferred . However, cost‐effectiveness studies of induction in LT remain extremely limited . Dopazo et al found comparable improvements in post‐LT renal function and rejection risk, but significant cost‐savings at their hospital in Spain, when using a low‐dose equine ATG (ATGAM; Pfizer) protocol vs standard basiliximab in recipients with pre‐LT renal impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In KT recipients, recently published economic evaluations of NDI and DI have been favorable, with ATG often being preferred . However, cost‐effectiveness studies of induction in LT remain extremely limited . Dopazo et al found comparable improvements in post‐LT renal function and rejection risk, but significant cost‐savings at their hospital in Spain, when using a low‐dose equine ATG (ATGAM; Pfizer) protocol vs standard basiliximab in recipients with pre‐LT renal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…However, cost‐effectiveness studies of induction in LT remain extremely limited . Dopazo et al found comparable improvements in post‐LT renal function and rejection risk, but significant cost‐savings at their hospital in Spain, when using a low‐dose equine ATG (ATGAM; Pfizer) protocol vs standard basiliximab in recipients with pre‐LT renal impairment. Further studies are needed to estimate the financial impact of a more uniform use of induction in adult LT recipients in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…When information was available, ≥78.1% of patients were White; the exception was Chauhan et al, in which 36.3–43.3% of patients across study arms were White [ 20 ]. The primary diseases at baseline varied between studies and study arms ( Table 4 ), but included alcoholism or ethanol abuse (23.1–71.4% across 3 studies [ 23 , 24 , 29 ]) hepatitis C virus infection (0–41.8% in 11 studies [ 7 , 19 , 20 , 22 26 , 28 30 ]), and hepatocellular carcinoma (2.3–63.6% in 10 studies [ 7 , 19 22 , 24 , 27 30 ]).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Renal function at baseline and during follow-up varied markedly between studies and treatment regimens ( Table 5 ). From baseline values, mean GFR/eGFR remained stable or improved over time in at least 1 study arm from 4 publications [ 18 , 22 , 23 , 29 ]. Mean±SD eGFR increased numerically from baseline in patients receiving tacrolimus+MMF+steroid+telbivudine (from 77.3 to 88.9 mL/min at 12 months [means within CKD stage 2] [ 18 ]) and in non-betel nut chewers receiving once-daily tacrolimus (from 72.2±21.9 to 77.8 mL/min/1.73 m 2 at 17 months [means within CKD stage 2] [ 23 ]).…”
Section: Renal Functionmentioning
confidence: 99%
“…All patients received MMF plus a bolus of corticosteroid (not followed by maintenance steroids). The incidence of acute cellular rejection (BPAR) and renal outcomes were better in the basiliximab group (104,105). Even though these studies have not been designed for NASH patients, however considering a higher incidence of renal dysfunction, low dose tacrolimus regimens should be considered in patients with NASH beyond 3 months as a strategy to prevent renal compromise post-LT.…”
Section: Post-transplant Renal Dysfunctionmentioning
confidence: 99%